Does trade liberalization reduce child mortality in low- and middle-income countries? A synthetic control analysis of 36 policy experiments, 1963-2005. (May 2018) - Barlow, Pepita
Abstract: Scholars have long argued that trade liberalization leads to lower rates of child mortality in developing countries. Yet current scholarship precludes definitive conclusions about the magnitude and direction of this relationship. Here I analyze the impact of trade liberalization on child mortality in 36 low- and middle-income countries, 1963–2005, using the synthetic control method. I test the hypothesis that trade liberalization leads to lower rates of child mortality, examine whether this association varies between countries and over time, and explore the potentially modifying role of democratic politics, historical context, and geographic location on the magnitude and direction of this relationship. My analysis shows that, on average, trade liberalization had no impact on child mortality in low- and middle-income countries between 1963 and 2005 (Average effect (AE): −0.15%; 95% CI: −2.04%–2.18%). Yet the scale, direction and statistical significance of this association varied markedly, ranging from a ∼20% reduction in child mortality in Uruguay to a ∼20% increase in the Philippines compared with synthetic controls. Trade liberalization was also followed by the largest declines in child mortality in democracies (AE 10-years post reform (AE10 ): −3.28%), in Latin America (AE10 : −4.15%) and in the 1970s (AE10 : −6.85%). My findings show that trade liberalization can create an opportunity for reducing rates of child mortality, but its effects cannot be guaranteed. Inclusive and pro-growth contextual factors appear to influence whether trade liberalization actually yields beneficial consequences in developing societies. Highlights: Impact of trade liberalization on child mortality is currently unclear. Analysis of this relationship using synthetic control method. There is no universal association between trade liberalization and child mortality. Impact of trade liberalization and child mortality varies substantially. Reductions in child mortality greatest in democracies, Latin America, and pre-1990.